Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Dan Sikap Remaja Tentang HIV-AIDS - Arif rahman; Nurul Jannah; Aya tullah (Ilmiah Institut Citra Internasional, 2023)
HIV(Human Immunodeviciency Virus) is a major global health problem has taken its toll died 40.1 lives so far. Indonesian Health Ministry recorded HIV cases in 2021 as many as 36.902 cases, majority patients are of productive age. Health education plays an important role in early HIV prevention. The purpose of this research to analyze the influence of health promotion on knowledge and attitudes of adolescents about HIV-AIDS. This research is a pre-Experimental study using One Group Pre-test-Post-Test Design. The research sample was 73 student. Knowledge level research results shows that respondents who have a high level of Pre-Test knowledge are 41.1% and Post-Tes results have increased are 61.6%, and respondents who have a low level of knowledge Pre-Test are 58.9% and Post-Test result. In respondents who have a positive attitude Pre-Test are 52.1% and Post-Test results have an increase are 71.2%. And respondents who have a low attitude Pre-Test are 47.9% and Post-Test results have decreased to 28.8%. Based on the Paired T-Test test, the level of knowledge and attitudes of adolescents towards HIV-AIDS before and after health promotion obtained each Asymptotic Significance Two Tails value or P Value are 0.000 <0.05. It is hoped that health education in schools can be carried out routinely to increase students' knowledge and attitudes in preventing HIV-AIDS.